2001
DOI: 10.1034/j.1600-0773.2001.d01-167.x
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium Phosphide Exposure: Implications on Rat Brain Lipid Peroxidation and Antioxidant Defence System

Abstract: Abstract:We investigated the effect of aluminium phosphide exposure (10 mg/kg body weight) on lipid peroxidation and antioxidant defence system in different regions of rat brain. A significant increase in lipid peroxidation in cerebrum, cerebellum and brain stem was observed in aluminium phosphide-exposed rats, which was accompanied by a marked decrease in the activities of antioxidant enzyme, superoxide dismutase and catalase. A decline in the activity of glutathione reductase was also observed, however, no c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
50
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 20 publications
14
50
0
1
Order By: Relevance
“…In this study, basal levels of LPx products measured as malondialdehyde (MDA) were found to be significantly increased after Al exposure in both the cerebrum and cerebellum (Table 4). Similar results were also observed in various laboratories after Al treatment to experimental animals (Dua and Gill 2001;Kaiser et al 2005;Nehru et al 2007;Albendea et al 2007). It is known that Al is a nonredox active metal (Zatta et al 2002), therefore cannot participate directly in oxidation.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, basal levels of LPx products measured as malondialdehyde (MDA) were found to be significantly increased after Al exposure in both the cerebrum and cerebellum (Table 4). Similar results were also observed in various laboratories after Al treatment to experimental animals (Dua and Gill 2001;Kaiser et al 2005;Nehru et al 2007;Albendea et al 2007). It is known that Al is a nonredox active metal (Zatta et al 2002), therefore cannot participate directly in oxidation.…”
Section: Discussionsupporting
confidence: 89%
“…Lipid peroxidation gives evidence for the attack of cell membranes by the evolved free radicals (Ferrari, 2000). In addition, glutathione in its reduced form is the most abundant intracellular antioxidant and is involved in scavenging free radicals or serving as a substrate for glutathione peroxidase enzyme that catalyzes the detoxification of H 2 O 2 (Dua and Gill, 2001). In the present study, significant changes in GSH were observed in the three studied brain regions after the two routes of EUD-NPs administration.…”
Section: Discussionsupporting
confidence: 47%
“…GSTs are essential components of the cellular antioxidant defence system, as they catalyze the conjugation of GSH to several dangerous compounds (Arrigo 1999;Rahaman et al 1999). As for the effect of metal ions on GST, conflicting results have so far been reported on both the activity and expression of the different GST classes in various tissues (Yousef 2004;Dua and Gill 2001).…”
Section: Introductionmentioning
confidence: 99%